Developing a pathway out of poverty in the Global Coffee Production Network - a case study of employment creation for baristas in the speciality coffee industry - Anderson, Robyn (Department of Sociology, 2017)
With a narrowly defined unemployment rate of 26.5% in South Africa, this paper contributes to the salient task of exploring a job creation programme in a high growth sector of the global coffee production network, namely the production of espresso based beverages by baristas for sale in restaurants, cafes, and hotels. Situated in the qualitative paradigm with an inductive research agenda, this research utilises the case study method to explore Ground UP, a skills training programme of a local not-for-profit, which provides barista skills training that unemployed people can use to become economically active in context of the specialty coffee industry. By applying the concepts of upgrading in the context of a global production network and a descriptive focus on both the Ground UP programme, as well as the characteristics and dynamics specialty coffee industry in South Africa, this research examines the potential for this industry to offer a pathway out of poverty. Applying a theoretical lens to this descriptive case study, the theme of governance features strongly, and the analysis reveals that Ground UP, as an agent of palliative development, can help beneficiaries to access a pathway out of poverty. It is also argued that the extent to which they will be able to capture the gains in the specialty coffee industry in the longer term will be impacted on external factors and other key players in the industry as well as their positioning in a global production network.